Exploring strength and ductility responses of beam-column joints using UHPC and UHPFRC employing concrete damaged plasticity (Fracture and Structural Integrity, 2024)
Structures subjected to severe loads, such as earthquakes, often develop cracks at the beam-column joints, underscoring the significance of these regions in design. This study focuses on a comparative analysis of beam-column joints constructed with Ultra-High-Performance Concrete (UHPC) and Ultra-High-Performance Fiber-Reinforced Concrete (UHPFRC) using the Finite Element Method (FEM) within the Abaqus software, contrasting with Low-Strength Concrete (LSC) and Normal-Strength Concrete (NSC). The results underscore the superiority of UHPFRC in compressive and tensile strength, coupled with enhanced ductility. Furthermore, distinct failure mechanism are observed in the concretes, captured by concrete damaged plasticity (CDP), leading to a deeper understanding of the behavior of these high-strength materials. These findings carry significant implications for enhancing structural safety and performance, particularly in situations involving seismic or other severe loads.
Keywords: Beam-column joints; UHPFRC; CDP; Ductility; failure